Effects on Plant Growth and Reproduction of a Peach R2R3-MYB Transcription Factor Overexpressed in Tobacco - Rahim, Md Abdur; Resentini, Francesca; Dalla Vecchia, Francesca; Trainotti, Livio (Frontiers in Plant Science, 2019)
In plants, anthocyanin production is controlled by MYB and bHLH transcription factors. In peach, among the members of these families, MYB10.1 and bHLH3 have been shown to be the most important genes for production of these pigments during fruit ripening. Anthocyanins are valuable molecules, and the overexpression of regulatory genes in annual fast-growing plants has been explored for their biotechnological production. The overexpression of peach MYB10.1 in tobacco plants induced anthocyanin pigmentation, which was particularly strong in the reproductive parts. Pigment production was the result of an up-regulation of the expression level of key genes of the flavonoid biosynthetic pathway, such as NtCHS, NtCHI, NtF3H, NtDFR, NtANS, and NtUFGT, as well as of the proanthocyanidin biosynthetic pathway such as NtLAR. Nevertheless, phenotypic alterations in transgenic tobacco lines were not only limited to anthocyanin production. Lines showing a strong phenotype (type I) exhibited irregular leaf shape and size and reduced plant height. Moreover, flowers had reduced length of anther’s filament, nondehiscent anthers, reduced pistil length, aborted nectary glands, and impaired capsule development, but the reproductive parts including androecium, gynoecium, and petals were more pigmented that in wild type. Surprisingly, overexpression of peach MYB10.1 led to suppression of NtMYB305, which is required for floral development and, of one of its target genes, NECTARIN1 (NtNCE1), involved in the nectary gland formation. MYB10.1 overexpression up-regulated JA biosynthetic (NtAOS) and signaling (NtJAZd) genes, as well as 1-aminocyclopropane-1-carboxylate oxidase (NtACO) in flowers. The alteration of these hormonal pathways might be among the causes of the observed floral abnormalities with defects in both male and female gametophyte development. In particular, approximately only 30% of pollen grains of type I lines were viable, while during megaspore formation, there was a block during FG1 (St3-II). This block seemed to be associated to an excessive accumulation of callose. It can be concluded that the overexpression of peach MYB10.1 in tobacco not only regulates flavonoid biosynthesis (anthocyanin and proanthocyanidin) in the reproductive parts but also plays a role in other processes such as vegetative and reproductive development.